Changes in Solid Phase Properties of Acid Soils as M fected by Limestone,Gypsum, Palm Oil Mill Effluent and Rock Phosphate Applications - Jusop, Shamsuddin; I., Jamilah; Abdul Hamid, Sharifuddin; Bell, L. C. (1992)
Ultisols and Oxisols in Malaysia are dominated by kaolinite and sesquioxides, which are characterized by high Al saturation, low ECEC and Ca and/or Mg deficiencies. These acid soil infertility factors are limiting to annual crop production on the soils. A pot experiment was conducted to investigate the chemical changes in solid phase propmies of some Malaysian Ultisols and Oxisols affected by limestone, gypsum, palm oil mill effluent and rock phosphate applications. Results obtained showed that the negative charge on the clay surface of the untreated samples increased with an increase in soil H. Limestone, palm oil mill effluent and rock phosphate applications increased soil pH, resulting in an increase in CECw The CECIJ in the palm oil mill effluent treatment was further increased by an increase in the soil solution ionic strength and by the protonation of carboxyl and/or hydroxyl groups present in the organic matter. Exchangeable Ca and Mg increased, while exchangeable Al decreased significantly after palm oil mill effluent and limestone applications. It was observed that exchangeable K was reduced by gypsum and rock phosphate applications.